2019
DOI: 10.1108/lodj-05-2018-0180
|View full text |Cite
|
Sign up to set email alerts
|

Strategic compatibility, collaboration and collective impact for community change

Abstract: Purpose Communities are best able to tackle complex social problems when solutions are achieved collaboratively. Inter-organizational partnerships are strongest and provide the greatest benefit to communities when the relationships are mutually compatible. The purpose of this paper is to introduce an evidence-informed approach to identifying and forming mutually compatible collaborations among organizations responsible for promoting community well-being and carrying out community-level interventions. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…The result of research in Table 4 has consistency with the theory of strategic collaboration describe that basically this approach may use to all level of the domain of the public sector to diminish the complexity through the actors' motivation and intentional to break the complex problems and getting the sustainability change for innovation [13], [36]. The results also showed each dimension have a mean value was above 3 (≥3.00), and Tukey's estimate of power to which observations achieve=3.497.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The result of research in Table 4 has consistency with the theory of strategic collaboration describe that basically this approach may use to all level of the domain of the public sector to diminish the complexity through the actors' motivation and intentional to break the complex problems and getting the sustainability change for innovation [13], [36]. The results also showed each dimension have a mean value was above 3 (≥3.00), and Tukey's estimate of power to which observations achieve=3.497.…”
Section: Resultsmentioning
confidence: 55%
“…The capacity of individual or community in making collaboration and synergy are necessary, so they should be enlarged. It revealed that the community collaboration model may significantly impact school improvement and sustainability [11]- [13]. Further, the performance of educational national standards and education quality service have determined by strategic collaboration approach [14].…”
Section: Introductionmentioning
confidence: 99%
“…One way to overcome the knowledge spillover effects faced by regional universities was suggested by M. E. Brown, T. Riz zuto, and P. Singh. Their research reveals the peculiarities of strategic compatibility, cooperation and collective influence of the European higher education system on societal changes [16]. The authors highlight the concept of "strategic compati bility assessment".…”
mentioning
confidence: 99%
“…Brown M. E., Rizzuto T., and Singh P. argue that the high er education system best solves complex social problems only when solutions are achieved by the joint efforts of higher edu cation institutions. An interuniversity partnership is sustain able and efficient when relations between universities are gov erned by the command and control structure of the Ministry of Education [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation